A frequency reconfigurable MIMO antenna with agile feedline for cognitive radio applications. Issue 3 (19th December 2019) - Riaz, Sharjeel; Zhao, Xiongwen; Geng, Suiyan
Abstract: A novel frequency agile multiple‐input‐multiple‐output (MIMO) patch antenna based on a reconfigurable feedline is proposed. The proposed antenna structure has two hexagonal‐shaped patch antenna elements. A defected ground structure having hexagonal shape is included in the ground plane to make the design compact and improve isolation among antenna elements. Further compactness is achieved using reactive loading. Frequency reconfigurability is realized by employing varactor diodes in the microstrip feedline. The proposed antenna achieves a frequency reconfigurable band with wide tuning range from 1.42 to 2.27 GHz with good gain and efficiency. Furthermore, an envelope correlation coefficient value of less than 0.2 and minimum isolation of 12 dB was achieved, displaying good MIMO performance. The presented antenna has a planar, low profile design with compact size of 100 × 50 mm 2 . Thus, frequency agility, wide range tuning, compactness, and planar structure of the proposed antenna design make it suitable for modern wireless handheld devices particularly in cognitive radio applications.